Predisposing, Enabling and Reinforcing Factors of Premarital Sex Behavior in School Adolescents (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Nowadays, 60% adolescents in Indonesia admitted that had practiced premarital sexbehavior and 50% of people living with HIV and AIDS are adolescent age group. Thenegative consequences of sex behavior which causes an Indonesian adolescent disruptedopportunities continue study at school, enter the work force, starting become a familyand become a member of society as well. Premarital intercourse makes unintendedpregnancy rates still high. Based on data obtained from the Pekanbaru City HIV-AIDSManagement Commission (KPA) in April 2017, it was found that HIV-AIDS caseshave always increased from year to year. The purpose of this study was to determinethe correlation between predisposing, enabling, and reinforcing factors with premaritalsex behavior in adolescents. The design was cross sectional study. This study was conductedAugust 2017 with multistage random cluster sampling and with 481 adolescentrespondents in 18 SMA in Yogyakarta City, which were analyzed using Chi Square test.There were a relationship of knowledge (p = 0.000, RP = 3.893), attitude (p = 0.000, RP= 7.240), self-esteem (p = 0.000, RP = 3.502), source of information (p = 0.003) and peerroles (p = 0.000, RP = 11.660) with premarital sex behavior. Meanwhile, there were norelation of family role (p = 0.436, RP = 0.823) and teacher role (p = 0.053 RP = 1.596)with premarital sex behavior. Knowledge, attitudes, self-esteem, information source andthe role of peers are related to premarital sex behavior. The role of the family and the roleof the teacher are not related to premarital sex in adolescents.